Estimated Pollutant Load from Nuclear and Energy Research Institute (IPEN/CNEN-SP, BRAZIL) - Tatiane Bernardino de Seixas Carvalho da Silva; Cintia Carvalho de Oliveira; Joyce Rodrigues Marques; Mainara Generoso Faustino; Thamiris Brandino Stellato; Lucilena Rebelo Monteiro; Maria Aparecida Faustino Pires; Marycel Elena Barboza Cotrim (Brazilian Journal of Radiation Sciences)
To quantify the pollutant load received by a water body is one necessary step to keep its original standards, irrespective to the releasing source. Thus, to monitor and control the amount of pollutants released in a water body assures the water will remain free from excessive pollution. Also, that no harm to human health and the environment will occur. Hence, this paper aims to estimate the pollutant load of sanitary wastewater released by the Nuclear and Energy Research Institute (IPEN / CNEN-SP) in 2015 and 2016. The analysis of Cd, Pb, Cu, Cr, Zn, Ba, Ni, Mn, Fe, B and Sn was performed by Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). These metals and the total fixed solids were used to estimate the pollutant load. Wastewater flow measurement was carried out using bromide (Br -) as tracer and with the values from IPEN`s annual water consumption. Since 2006, this is performed as part of the Environmental Monitoring Program (PMA-Q). In compliance with the current Brazilian Environmental Legislation and with the Term of Conduct Adjustment requirements, agreed with the Brazilian Institute of Environment and Renewable Natural Resources (IBAMA). Even the pollutants load has increased in 2015 and 2016, the monitoring frequency and water consumption has diminished in the last years. These facts increase the uncertainties in the monitoring and could lead to non-compliances with the monitoring laws.